The first equation y = 3x-10 basically says that y is the same as 3x-10. This will allow us to make a replacement in the second equation. This is what the substitution rule allows us to do.
2x + 3y = 3
2x + 3( y ) = 3
2x + 3( 3x-10) = 3 ... replace y with 3x-10
2x+3(3x) + 3(-10) = 3 ... distribute
2x + 9x - 30 = 3
11x - 30 = 3
11x-30+30 = 3+30 ... add 30 to both sides
11x = 33
11x/11 = 33/11 ... divide both sides by 11
x = 3
Now that we know x = 3, we use it to find the value of y. You can use any equation with x and y in it. The easiest is where y is already isolated
y = 3x - 10
y = 3*3 - 10 ... replace x with 3
y = 9 - 10
y = -1
Final Answer: choice D; the ordered pair (3,-1)